Linear Accelerator-Based Stereotactic Radiotherapy for Low-Grade Meningiomas: Improved Local Control With Hypofractionation. (April 2019) - Wegner, Rodney E; Hasan, Shaakir; Abel, Stephen; Anderson, Sidney; Fuhrer, Russell; Williamson, Richard W; Karlovits, Stephen M
Background and purpose: Meningioma is a common type of benign tumor that can be managed in several ways, ranging from close observation, surgical resection, and various types of radiation. We present here results from a 10-year experience treating meningiomas with a hypofractionated approach. Materials and methods: We reviewed the charts of 56 patients treated with stereotactic radiosurgery (SRS) or hypofractionated stereotactic radiotherapy (SRT) from 2008 to 2017. A total of 46 (82%) patients had WHO Grade 1 disease and 10 (18%) had Grade 2. Outcomes that were analyzed included local control rates and the rate and grade of any reported toxicity. Results: A total of 38 women and 18 men underwent SRS to a median dose of 15 Gy (n = 24) or hypofractionated SRT with a median dose of 25 Gy in five fractions (n = 34). Of the 56 patients, 22 had surgery before receiving treatment. The median follow-up was 36 (6-110) months. Local control at 2 and 5 years for all patients was 90% and 88%, respectively. Comparing fractionated to single-fraction treatment, there was improved local control with fractionation (91% vs 80% local control at 2 years, P  = .009). There was one episode of late radionecrosis on imaging with associated symptoms after single-fraction treatment and one patient requiring resection of meningioma related to worsening symptoms (and local recurrence) after five-fraction SRT. Conclusions: This study provides further evidence for high rates of local control and minimal toxicity using a hypofractionated SRT approach, with improvement in local control through use of hypofractionation.